Mesoscale boundary layer development over mountainous terrain - Bader, David C., author (Colorado State University. Libraries, 1985)
The diurnal evolution of the mesoscale boundary layer ( ~ 50 km) over gently sloping terrain upwind of a high mountain barrier is described using both observational data and results from numerical model simulations . Atmospheric sounding data are presented from two nights , one during the summer and the second during the winter, when the mesoscale nocturnal boundary layer development was observed . Subsequently, a series of two and three-dimensional numerical model experiments are presented which identify the important physical processes responsible for the observed features. A conceptual model of mesoscale boundary layer evolution is then presented that accounts for the principle dynamic mechanisms discerned from analysis of the observational and simulated cases. Observational data from both nights reveal that the nocturnal boundary layer (NBL) extends 200-500 m above the valley ridgetops and plateaus and cools 1-4 K. Found within this layer are topographically induced thermal winds of 1-5 m s-l which either produce mesoscale circulations or influence the prevailing synoptic wind fields. The summer night data reveal that when the prevailing geostrophic wind is less than 7-10 m s-l at 500 mb and contains ro component into the high barrier, a complete mountain-plain circulation forms over the plateaus and ridges and down valley winds in ·the underlying valleys are strong. Contrasted with this is the winter case in which a much stronger geostrophic wind ( ~ 15 m s-l at 500 mb) directed into the barrier inhibited the mountain-plain circulation . In this case, there was a wide mesoscale variability in nocturnal boundary layer structure . One numerical experiment realistically simulated the diurnal evolution of the mesoscale boundary layer through a complete cycle encompassing the evening and morning transition periods. Additional simulations reveal that surface cooling and the shear between low-level thermal f lows and the overlying winds produce a 300 -500 m deep NBL 3-5 h after sunset. The nocturnal stable layer contains decoupled wind regions and can form a blocked wind region upwind of the barrier. In all cases, the nocturnal thermal wind component was 4-5 m s-l directed away from the barrier. It is also demonstrated that full three-dimensional model configuration are necessary to adequately describe the evolution of three-dimensional boundary layer structure.
November 1985.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1985.
Keywords: Boundary layer (Meteorology); Atmospheric circulation -- Colorado; Mesometeorology -- Colorado